2019
DOI: 10.7567/1347-4065/ab25ba
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability study of Ni–Si silicide films on Ni/4H-SiC contact by in-situ temperature-dependent sheet resistance measurement

Abstract: We investigate the Ni–Si film silicidation process on 4H-SiC and Si substrates and compare the thermal stability of the films grown on each substrate. The Ni–Si films were subjected to rapid thermal annealing (RTA) in the temperature range 575 °C–975 °C for 90 s, and their thermal stability was characterized by in-situ temperature-dependent sheet resistance measurements at temperatures of 25 °C–550 °C. The sheet resistance of a 40 nm thick Ni film was observed to increase sharply above 330 °C in the Ni/Si (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Ni/H-diamond possess good thermal stability even after annealing at temperatures as high as 900 °C for 10 min, which is comparable with those of the Ni/SiC contacts [21,22]. Comparing with the output currents of the 500 °C-annealed and 700 °C-annealed Ni/H-diamonds at ±1.0 V, those for the 900 °C-annealed one decreased slightly.…”
Section: R Peer Review 5 Ofmentioning
confidence: 57%
See 1 more Smart Citation
“…Ni/H-diamond possess good thermal stability even after annealing at temperatures as high as 900 °C for 10 min, which is comparable with those of the Ni/SiC contacts [21,22]. Comparing with the output currents of the 500 °C-annealed and 700 °C-annealed Ni/H-diamonds at ±1.0 V, those for the 900 °C-annealed one decreased slightly.…”
Section: R Peer Review 5 Ofmentioning
confidence: 57%
“…The R S and ρ C for the Ni/H-diamond after annealing at 700 • C are calculated to be Figure 4a shows the current-voltage curves of the Ni/H-diamond after annealing at 900 • C. All the curves have good linear relationships. Therefore, the ohmic contacts of the Ni/H-diamond possess good thermal stability even after annealing at temperatures as high as 900 • C for 10 min, which is comparable with those of the Ni/SiC contacts [21,22].…”
Section: Resultsmentioning
confidence: 81%
“…The thickness of NiSix used as the bottom-side electrode was determined to be approximately 100 nm. In a previous study [24], it was reported that A nickel (Ni) film was deposited on the backside of the wafer to form electrodes, and the annealing process was conducted for one minute at 950 °C for ohmic contact, after which Pd was deposited for 2 min at 300 W power with shadow masks of three different patterns in order to form the front Pd electrodes. The SiC substrates (hydrogen sensors) were attached to the quartz plates within a 3 × 3 cm 2 area and were finished with wire bonding.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of NiSix used as the bottom-side electrode was determined to be approximately 100 nm. In a previous study [24], it was reported that The sensors are made of a MIS structure. Pd film with a thickness of 200 nm was deposited over the Ta 2 O 5 layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation